Українська національна ідея та її значення для утвердження державної незалежності України - Павличко, Д. (Народна творчість та етнографія, 2005)
This article is an analysis of the historical development of national idea as general term and the role that it plays in the formation of the ethnos. The author is trying to give a detailed overlook of the development of the Ukrainian ethnos by analyzing some important and complicated historical events. At the same time author is concentrating an attention of the readers on the most important questions of contemporary times (including Europiazation of Ukraine, language issue, particularities of Ukrainian East and West and its unity). He underlines the importance of the understanding of the fact that Ukrainians have common conciseness independently from their geographical location.